Amager Resource Centre - Arquitectura, tecnologia e sustentabilidade - Miguel Sousa Rebelo (2017)
Times are changing. And architecture will change with it.There are places where this evolution is more predictable,visible or tangible than others. Copenhagen is an example of it:it's a happy, liveable, clean, safe, sustainable and efficient city.And the architecture in Copenhagen reflects this social,economical and political panorama. The Amager Bakke itself isthe architectural celebration of it. It's a milestone for the cityand for the citizens' achievements and an efficient way topromote and materialize this society's hedonistic lifestyle.Therefore, as an infrastructural building that fulfils the city'senergetic needs, it creates a public space and a landmark in thecity, building a new social paradigm for architecture. We areinterested in studying the dynamics associated to this particularrole of architecture: the social reflection of our time, thecontemporaneity.And for the sake of the architecture for people, we proposedouselves to dissect this building, its intervenient and its contextin order to understand what makes it so complex and multiplural in its conception. As a consequence, we willevidence the main controversial ingredients that create thisbig alchemy: the playful roof as an extension of thecity's landscape and the sociological empowerment inherentto cities' infrastructures interventions.As a result, ARC creates, at first, the opportunity for discussion,and ends up, instigating a deeper reflexion of what architecturecan do to involve people, their needs and their dreams.Furthermore, how architecture will go along with the biggestrevolution of this century and who knows the biggest sincehuman life exists: the permanent evolution of technology. Andsince we are nowadays, more and more aware and concernedabout how much our life and our cities will change in thefuture...The question now is: How do we want to live? We strongly believeArchitecture could have a huge impact on it.